Effectiveness of practice in mind program on standing shot and jump shot performance in elite netball players / Nur Asmidar A Halim and Mazlan Ismail - A Halim, Nur Asmidar; Ismail, Mazlan (Universiti Teknologi MARA, 2021)
Practice in Mind (PIM) training help to resolve physical and psychological problem in sport skills performance. Therefore, the present study was done to investigate the effectiveness of PIM training on netball standing shot and jump shot performances. Twenty state level netball shooters with 3 to 5 years playing experiences participated in this experimental study. Participants were randomly assigned into PIM training group and control group with 10 participants for each group. Both groups completed 18 training sessions in 3 times a week for 6 weeks intervention program. Pre, post, and retention test were conducted prior to the 10 standing and jump shooting task. The results revealed that there was significant different of PIM training group versus control group for both standing shot (p < .05) and jump shot (p<0.5) after 6 weeks. However, no significant different was observed after retention (week 12) for both groups. Based on the finding, it is suggested this present study will be beneficial to the athletes in terms of educating them about the importance of systematic imagery training to increase shooting performance in netball and for further improvement on their shooting techniques. Future studies are warranted to explore potential benefits of PIM training by focusing on a larger exposure and other netball specific motor-abilities.